WHO IS ENGAGED IN E-WOM? ROLE OF E-LOYALTY, DEMOGRAPHICS, VISIT FREQUENCY AND PRODUCT CATEGORY - (:unkn) unknown (My University, 2019)
Consumers tend to share their post-purchase experiences (WOM- Words of Mouth)with others regardless of whether the experiences are positive or negative. With theadvancement of internet technology, WOM behavior has shifted to online platforms(eWOM) and eWOM has become an extremely effective way of communication. The mainpurpose of this study is to unveil the antecedents of eWOM behavior. In this respect, therole of e-loyalty in addition to demographics and other relevant factors such as e-retailervisit frequency and consumer’s mostly purchased product online in eWOM behaviorwas examined. A total of 296 individuals were accessed beginning from January 2019 toFebruary 2019 through online convenience sampling. IBM SPSS 22 statistical softwarewas used and multiple regression models was applied. The independent variables wereable to explain the eWOM behavior with a R2value of.42. Compared to participants whobelonged to 36-45 age group, younger participants were less likely engaged in eWOMbehavior. Consumers who mostly purchased books, CDs, and electronic goods were morelikely engaged in eWOM behavior, compared to consumers making apparel purchasesonline. Finally, findings also revealed that the less the consumers visited online e-retailers,the less these eWOM behaviors were displayed.
E-WOM DAVRANIŞINI KİM SERGİLER? E-SADAKATİN, DEMOGRAFİKLERİN, ZİYARET SIKLIĞININ VE ÜRÜN KATEGORİSİNİN ROLÜ